Strategi Kolaboratif dalam Transformasi Pendidikan: Sebuah Perspektif Naratif dalam Mengatasi Tantangan TIK di Era Kurikulum Merdeka - Bian, Yullyatty; Lilianti, Lilianti; Rasid, Rasid (LP3M, Universitas Muhammadiyah Kendari, 2025)
This study aims to identify and analyze collaborative strategies to address the challenges of implementing Information and Communication Technology (ICT) in the era of the Merdeka Curriculum, using a narrative perspective approach. The Merdeka Curriculum emphasizes the integration of ICT as a supporting tool for more independent and innovative learning; however, challenges such as limited infrastructure, a lack of digital skills among teachers, and insufficient collaborative support remain obstacles in the field. This research employs a qualitative method with in-depth interviews involving Teacher Leaders and School Leaders in Kendari City. The results indicate that collaboration among teachers, schools, parents, and government is key to optimizing the application of ICT, particularly through support in providing training, enhancing competencies, and ensuring adequate equipment availability. These findings underscore the importance of collaborative strategies that involve various stakeholders in efforts to achieve sustainable educational transformation in the digital era, supporting the effectiveness of the Merdeka Curriculum.